Effects of Soil and Water Conservation Practices and Slope Gradient on Selected Soil Physicochemical Properties in Ejersa Watershed, Toke Kutaye District, Ethiopia - Negesu Kebede; Alemayehu Negassa (Applied and Environmental Soil Science)
This study was conducted to assess the effects of soil and water conservation practices and slope gradients on selected physicochemical properties of soil at Ejersa Watershed based on a total of 18 composite soil samples collected and analyzed using standard laboratory procedures. The values of pH, electrical conductivity, cation exchangeable capacity, organic carbon, organic matter, total nitrogen, and available phosphorus determined in soil samples collected from conserved and nonconserved plots were 6.4 and 6.16, 40.26 mS/m and 15.12 mS/m, 33.51 meq/100 g and 21.56 meq/100 g, 2.66% and 2.24%, 4.58% and 3.86%, 0.24% and 0.15%, and 29.45 ppm and 17.68 ppm, respectively. Soil pH, electrical conductivity, moisture, total nitrogen, and available phosphorus were significantly different (p<0.01) between treated and untreated plots and among the slope classes. Values of soil organic carbon and organic matter showed significant differences (p<0.05) between land types but not among the slope classes. Soil cation exchange capacity showed significant difference (p<0.05) between land types as well as among the slope classes. Relatively, higher values of many of the physicochemical parameters were recorded in samples collected from the treated land and lower slopes which might be attributed to the deposition effects of the conservation practices and decline in the rate of soil erosion.